Approach to Tremor Disorders - Lee, Andrea; Sarva, Harini (Seminars in Neurology, 2021)
Tremor disorders are diverse and complex. Historical clues and examination features play a major role in diagnosing these disorders, but diagnosis can be challenging due to phenotypic overlap. Ancillary testing, such as neuroimaging or laboratory testing, is driven by the history and examination, and should be performed particularly when there are other neurological or systemic manifestations. The pathophysiology of tremor is not entirely understood, but likely involves multiple networks along with the cerebello-thalamo-cortical pathways. Treatment options include medications, botulinum toxin, surgery, and nonpharmacologic interventions utilizing physical and occupational therapies and assistive devices. Further work is needed in developing accurate diagnostic tests and better treatment options for tremor disorders.
Keywords: tremor; pathophysiology; workup; treatments